Prima K I Yahya PhD - Gill, Philip; Yahya, Kharisma; Moniruzzaman, Monir (Cranfield University, 2018)
Graphene oxide interaction with nitrate esters for novel propellant formulation
Keywords: 'Nitrocellulose'; 'PhD'; 'Graphene'; 'Propellants'; 'Graphene Oxide'; 'nanomaterials show'; 'Chemical Thermodynamics and Energetics'